Detection of Novel Candidate Mutations as a Cause of Steroid-resistant Nephrotic Syndrome in Children Using Next-generation Sequencing Techniques - Alsanie, Walaa F.; Alamri, Abdulhakeem S.; Sobahy, Turki M.; Zailaie, Samar A.; Alhomrani, Majid; Refat, Moamen S.; Habeeballah, Hamza; Asdaq, Syed Mohammed Basheeruddin; Sreeharsha, Nagaraja; Gaber, Ahmed (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Objectives: Steroid-resistant nephrotic syndrome (SRNS) is a serious chronic ailment that affects children and causes blood coagulation issues as well as an increased vulnerability to infections. Only around 10% of inherited genetic nephrotic syndrome cases are responding to steroid therapy, and, accordingly, 90% of SRNS patients have multidrug resistance. This study was done to detect novel candidate mutations as a factor for causing SRNS in children using the sequencing technique. Materials and Methods: This study included nine children ranging in age from one to sixteen years old who had a clinical diagnosis of SRNS. Phenotype-genotype correlations in these Saudi children were explored using next-generation sequencing techniques to assess the correlation and/or effect of mutations in multiple genes on phenotype variability. The enrichment analysis was carried out to identify genes. Results: Five genes were potentially new causative agents for SRNS. The enrichment analysis helped us identify nine causal genes, not previously reported, in six out of nine individuals (66%). These genes are phospholipase D family member 3, mitogen-activated protein kinase binding protein 1, solute carrier family 12 members 3, ezrin, and pancreatic lipase related protein. The other four nominee genes were wilms tumor 1, diacylglycerol kinase iota, coenzyme Q8B, and CASC3. Conclusion: The outcome of the study indicated that there is a new mutation as we had four replicates for each sample run on a different sequencing lane. The histopathological findings of these mutated patients were focal segmental glomerulosclerosis.
Keywords: Next-generation sequencing; Steroid-resistant nephrotic syndrome; Focal; segmental glomerulosclerosis; Gene mutation; Pediatric